1997
DOI: 10.1002/etc.5620161006
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity identification evaluations of produced‐water effluents

Abstract: Abstract-Toxicity identification evaluations (TIEs) were performed on 14 produced-water (PW) samples of various salinities from inland and offshore oil-and gas-production facilities operated by different companies in Wyoming, Texas, California, and Louisiana (USA) to evaluate the efficacy of TIE procedures in determining potential toxicants in PW effluents. The research involved acute (24-and 48-h) freshwater and marine toxicity tests on whole PW and PW fractions generated by standard U.S. Environmental Protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
(28 reference statements)
1
22
0
Order By: Relevance
“…Microcrustaceans, Ceriodaphnia dubia Richard, were chosen as the assessment species for this study because they are sensitive to many constituents commonly found in NGSPWs and are routinely used in toxicity testing required by NPDES permits (USEPA 1995;Sauer et al 1997). C. dubia, commonly named 'water fleas', are freshwater arthropods that occur in littoral areas of lakes, ponds, and marshes throughout the world.…”
Section: Identify Constituents Of Concernmentioning
confidence: 99%
“…Microcrustaceans, Ceriodaphnia dubia Richard, were chosen as the assessment species for this study because they are sensitive to many constituents commonly found in NGSPWs and are routinely used in toxicity testing required by NPDES permits (USEPA 1995;Sauer et al 1997). C. dubia, commonly named 'water fleas', are freshwater arthropods that occur in littoral areas of lakes, ponds, and marshes throughout the world.…”
Section: Identify Constituents Of Concernmentioning
confidence: 99%
“…Other sources of toxicity include major ion imbalances, hydrocarbons, ammonia, and hydrogen sulfide (Boelter et al 1992;Sauer et al 1997;Elias-Samlalsingh et al 2004). Gulley et al (1992) and Mount et al (1992) found that toxicity resulting from major ion salinity could be accurately predicted and accounted for using statistically-derived ion toxicity models.…”
Section: Task 20 -Toxicity Identification Evaluation Of Produced Watmentioning
confidence: 99%
“…Of those studies that have assessed the effects of produced water on freshwater organisms, elevated ion concentrations, organics and ammonia have been identified as the primary constituents causing observed toxicity (Ho and Caudle 1997;Sauer et al 1997), and each of these components could be significantly modified upon entering a receiving system. However, field studies that validate these laboratory-based effects are practically nonexistent.…”
Section: Introductionmentioning
confidence: 99%
“…Produced water is an inextricable part of the hydrocarbon recovery processes; yet, it is by far the largest volume waste stream associated with hydrocarbon recovery (Sauer et al 1997;Balaam et al 2009;Fakhru'l-Razi et al 2009). …”
Section: Introductionmentioning
confidence: 99%